Invisible esthetic ortodonthics - Chávez Sevillano, Manuel Gustavo (2007)
The adult usually offers resistance to the conventional orthodontic treatments, due to the need of using visible brackets such as metallic or esthetic porcelain. The concept of Invisible esthetic Orthodontics or Lingual Orthodontics covers the expectations of this type of patient. The multibrackets technique with lingual instruments is approximately 25 years old and with the experience of the treated cases, we have conceived a totally formal technique. This article it is an up-to-date revision of the different publications of Lingual Orthodontics, where one keeps in mind the history and the development of the lingual appliance, the diagnosis and treatment plan, the clinical and laboratory phases, the lingual mechanotherapy, the current tendencies and perspectives of the future of the lingual technique.